Circulating microRNAs are deregulated in overweight/obese children: preliminary results of the I.Family study - Iacomino, Giuseppe; Russo, Paola; Stillitano, Ilaria; Lauria, Fabio; Marena, Pasquale; Ahrens, Wolfgang; De Luca, Pasquale; Siani, Alfonso (Genes & nutrition, 2016)
BACKGROUND: MicroRNAs (miRNAs) are small non-coding RNAs involved in the modulation of gene expression and in the control of numerous cell functions. Alterations of miRNA patterns frequently occur in cancer and metabolic disorders, including obesity. Recent studies showed remarkable stability of miRNAs in both plasma and serum making them suitable as potential circulating biomarkers for a variety of diseases and conditions. The aim of this study was to assess the profile of circulating miRNAs expressed in plasma samples of overweight or obese (OW/Ob) and normal weight (NW) prepubertal children from a European cohort (www.ifamilystudy.eu). The project, aimed to assess the determinants of eating behavior in children and adolescents of eight European countries, is built on the IDEFICS cohort (www.ideficsstudy.eu), established in 2006. Among the participants of the I.Family Italian Cohort, ten OW/Ob (age 10.7 ± 1.5 years, BMI 31.6 ± 4.3 kg/m²) and ten NW (age 10.5 ± 2.7 years, BMI 16.4 ± 1.7 kg/m²) children were selected for the study. Gene arrays were employed to differentially screen the expression of 372 miRNAs in pooled plasma samples. Deregulated miRNAs (p < 0.05) were further validated in the individual samples using a real-time PCR (RT-qPCR) approach. RESULTS: Using a significance threshold of p < 0.05 and a fold-change threshold of ± 4.0, we preliminarily identified in the pooled samples eight miRNAs that differed between the OW/Ob and NW groups. The validation by RT-qPCR in the individual plasma samples showed a twofold upregulation of miR-31-5p, a threefold upregulation of miR-2355-5p, and a 0.5-fold downregulation of miR-206 in OW/Ob as compared with NW. The molecular functions of these differentially expressed plasma miRNAs as well as their expected mRNA targets were predicted by bioinformatics tools. CONCLUSIONS: This pilot study shows that three circulating miRNAs are differentially regulated in OW/Ob as compared with NW children. Although causal pathways cannot be firmly inferred by these results, that deserve confirmation in larger samples, it is conceivable that circulating miRNAs may be novel biomarkers of obesity and related metabolic disturbances.